Adolescent experiences of pregnancy in low-and middle-income countries: a meta-synthesis of qualitative studies - Rachel Crooks; Carol Bedwell; Tina Lavender (BMC, 2022)
Abstract Background Fertility rates among adolescents have fallen globally, yet the greatest incidence remains in low-and middle-income countries (LMICs). Gaining insight into adolescents needs and experiences of pregnancy will help identify if context specific services meet their needs and how to optimise pregnancy experiences. A meta-synthesis of qualitative studies considering adolescent experiences of pregnancy in LMICs has not yet been published. Aim To synthesise available qualitative evidence to provide greater understanding of the needs and experiences of adolescents who become pregnant in low-and middle-income countries. Methods An extensive search utilised six databases and citations searching. Studies were included if they were of a qualitative or mixed methods design. Participants lived in LMICs and were adolescents who were pregnant, had experienced pregnancy during adolescence or were an adolescent male partner. Relevant studies were assessed for quality to determine suitability for inclusion. A meta-ethnography approach was used to generate themes and a final line of argument. Results After screening and quality assessment 21 studies were included. The meta-ethnography generated four themes, A wealth of emotions, I am not ready, Impactful relationships and Respectful and disrespectful care. Unplanned, unwanted and unacceptable pregnancies were a source of shame, with subsequent challenging personal relationships and frequently a lack of needed support. Even when pregnancy was wanted, adolescents faced the internal conflict of their desires not always aligning with socio-cultural, religious and family expectations. Access, utilisation and experiences of care were significantly impacted by adolescents' relationships with others, the level of respectful care experienced, and engagement with adolescent friendly services. Conclusions Adolescents who experience pregnancy in LMICs deserve support to meet their personal and pregnancy needs; efforts are needed to tailor the support provided. A lack of a health care provider knowledge and skills is an obstacle to optimal support, with more and better training integral to increasing the availability of adolescent friendly and respectful care. Adolescents should be involved in the planning of health care services and supported to make decisions about their care. The diversity across countries mean policy makers and other stakeholders need to consider how these implications can be realised in each context.